Sensitivity analysis and proportioning design of rock burst similar materials - Yongsheng Liu; Jin Li; Qiulan Wu; Wang Liu (Functional Materials, 2017)
The rock burst similar material were prepared by quadratic orthogonal design. Sand ratio (A), cement plaster ratio (B), watered rate (C) are used as the level influence factors, and the uniaxial compressive strength C, the ratio of compressive and tensile strength and the impact energy index was used as assessment index. The sensitivity of the influence factors to the rock burst tendency of similar materials was studied by the range analysis method. The results showed that: sand ratio (A) is the main influence factors to the compressive strength of rock burst material; the ratio of water (C) is the main influence factor to the compressive and tensile strength ratio; cement gypsum ratio (B) is the main influence factor to impact energy index.